“To engraft ourselves on foreign stocks”: Byron’s Poetics of Acculturation - Schoina, Maria (Romanticism on the Net)

(untitled) (Université de Montréal, 2006)
AbstractConsidering the largely unacknowledged connection between Byron and Mary Shelley on the logistics which pertain to the experience of crossing-over cultures, this paper investigates the notion of authentic Italianisation as exemplified in their related texts, and discusses its problematics in the context of the dominant themes and preoccupations in Romantic culture. Thus, on the one hand, my paper examines how the Romantic anticipation of being immersed in local culture and of “going native” is articulated – or rather, performed – by Byron himself, by considering specific rhetorical strategies and figures of filiation he used to ground his relationship to Italian place. More specifically, I contend that although Byron’s polymorphic identification to Italian place is constructed in the imagination, it is also grounded in time- and space-bound actions and involves a structure of social relations. On the other hand, the paper delineates how Byron’s idiosyncratic immersion into Italianness is theorised by Mary Shelley and counted on as a model of second culture acquisition.